Zdvořilý řečový habitus jako sociokulturní regulativ vztahové sítě IV.: Sociální zoom, jeho předpoklady a evoluce - Slowik, Miroslav (Lidé města, 2019)
This article deals with the face-to-face relation as the necessary and sole axiomatic definition of the human world. The human world, primarily perceived through the perspective of evaluating the world through the relation to the Other, is a cultural and biological construct. The face carries a specific world view that is necessarily formed through its relation to other faces. The human face is a prerequisite for the origin of language, which is exuded by the face, thus being both a product of the animal world as well as strategic human behaviour encoded in the language. Modern man and their behaviour is the result of the evolution of social zoom, a process that determined present-day civilisation solely on the basis of the evolution of a balancing mechanism, i.e. altruistic language behaviour.